European-wide Formation and Certification for the Competitive Edge in Integrated Design - Riel, A.; Tichkiewitch, S.; Messnarz, R. (Cranfield University Press, 2009)
Competitive Product Design is more and more linked to mastering the challenge of the complexity and multidisciplinary nature of modern products in an integrated fashion from the very earliest phases of product development. Design Engineers are increasingly confronted with the need to master several different engineering disciplines in order to get a sufficient understanding of a product or service. Industrialists demand for the certification of these skills, as well as for their international recognition and exchangeability. This paper describes the approach that EMIRAcle takes together with the ECQA in order to define and establish job roles, curricula and certifications in the domain of Integrated Engineering on a European level.
Organised by: Cranfield University
Keywords: Integrated Engineering; Integrated Design Engineer; System Competence; System Competence, Product Development Improvement; Lifelong Learning; Certification; Professional Training